2005
DOI: 10.1200/jco.2005.04.275
|View full text |Cite
|
Sign up to set email alerts
|

Patient Online Self-Reporting of Toxicity Symptoms During Chemotherapy

Abstract: Patients are capable of reporting symptoms experienced during chemotherapy using a Web-based interface. Assessment in the clinical trial setting and comparison of direct patient- versus clinician-based approaches for reporting symptoms and their severity are warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
230
1
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 280 publications
(236 citation statements)
references
References 29 publications
4
230
1
1
Order By: Relevance
“…Whatever the case, we should take into account these confounding factors when assessing CIPN as a PRO, especially after breast surgery. In this respect, it is interesting to note that, in the study by Basch et al [2], it was feasible to collect PROs about pain, fatigue, nausea, vomiting, diarrhea, constipation, or ECOG PS through a web-based patient-reporting system during chemotherapy with the use of a patient version of the NCI-CTCAE that adapted suitable language for patient self-reporting and with a provision for teaching sessions, and technical support contact information. Further studies should investigate whether a similar approach could be effective for the assessment of CIPN.…”
Section: Discussionmentioning
confidence: 98%
“…Whatever the case, we should take into account these confounding factors when assessing CIPN as a PRO, especially after breast surgery. In this respect, it is interesting to note that, in the study by Basch et al [2], it was feasible to collect PROs about pain, fatigue, nausea, vomiting, diarrhea, constipation, or ECOG PS through a web-based patient-reporting system during chemotherapy with the use of a patient version of the NCI-CTCAE that adapted suitable language for patient self-reporting and with a provision for teaching sessions, and technical support contact information. Further studies should investigate whether a similar approach could be effective for the assessment of CIPN.…”
Section: Discussionmentioning
confidence: 98%
“…An alternative is to progress towards patient-initiated follow-up by adopting a symptom tracking process that can be used to provide control to patients with the continued safety of professional supervision in this monitoring. At the Memorial Sloan-Kettering Cancer Center in New York, USA, a Symptom Tracking and Reporting for Patients (STAR) program has been introduced to facilitate follow-up consultations [38]. The National Cancer Institute Common Terminology Criteria for Adverse Events schema for seven common symptoms has been adapted into a web-based patient-reporting system, accessible from desktop computers in outpatient clinics and from home computers.…”
Section: How This Evidence Is Being Utilisedmentioning
confidence: 99%
“…Guidelines for patient-reported assessment of outcomes were used to facilitate comprehension by respondents [30][31][32], which was tested using open-ended interviews (n = 6) with patients from the UK diagnosed with NSCLC who confirmed that they understood the survey and were willing to trade off among the attributes and levels.…”
Section: Development Of the Conjoint Tasksmentioning
confidence: 99%